Physical properties, Chemical Composition and Antimicrobial Activity of Oil and Extracts from Tetracarpidium conophorum (African Walnut) - Yangomodou, Oluwapamilerin Damola; Akinhanmi, Y.O. Uthman; Solana, O. I.; Olugbemi, M. T.; Ferry, Natalie; Hadfield, John A. (NIU Journal of Social Sciences, 2020)
The oil of the powdered nut of African walnut ( Tetracarpidium conophorum ) was extracted sequentially using the expeller press (mechanical) method and solvent extraction (chemical) method by soxhlet extractor. The physical appearance of the oil reveals that African walnut oil was pale yellow in colour, clear, light without impurities. The colour of the oil extract reveals that the petroleum ether extract was golden yellow, n-hexane extract was golden brown and chloroform extract was golden/dark brown. 200g of African walnut extracted by expeller press yielded 12.53 % of oil, 30 g of the sample extracted by hexane, petroleum ether and chloroform yielded 18.06 %, 12.5 % and 11.97 %. The chemical properties of the expeller pressed oil showed the saponification values, unsaponifiable matter content, acid value, peroxide values, free fatty acids (FFA), iodine, refractive index (RI) and specific gravity (SG) of the oil was 170.1 mg KOH g -1 , 4.1 g/kg -1 , 0.92 mg KOH g -1 , 1.02 meq O 2 kg -1 , 0.56 %, 91.3 Wij’s, 1.445 and 0.94. The n-hexane extract had 174.1 mg KOH g -1 , 3.9 g/kg -1 , 0.72 mg KOH g -1 , 1.01 meq O 2 kg -1 , 0.46 %, 90.1 Wij’s, 1.442 and 0.88. Petroleum ether extract had 165.1 mg KOH g -1 , 2.5 g/kg -1 , 0.82 mg KOH g -1 , 1.00 meq O 2 kg -1 , 0.65 %, 87.6 Wij’s, 1.440 and 0.94. Chloroform extract had 160.1 mg KOH g -1 , 3.2 g/kg -1 , 0.62 mg KOH g -1 , 0.94 meq O 2 kg -1 , 0.82 %, 89.9 Wij’s, 1.440 and 0.94. The oil could be exploited for use in vegetable oil and cosmetic industries. In this study, the  in vitro  antimicrobial activities of African walnut oil and extracts were evaluated using agar-well diffusion method against clinical isolates of Staphylococcus aureus , Escherichia coli, Cutibacterium acne, Malassezia furfur and Candida albicans which were isolated from human skin infections. The results of the investigation revealed that African walnut oil had inhibitory effect on the growth of all the test microorganisms. On the bacterial species, S. aureus was highly inhibited by African walnut oil as confirmed by the zones of inhibition measured. C. acnes was moderately inhibited, while the growth of E. coli was observed to be mildly inhibited. With the fungal species, 100 % of African walnut oil proved really effective inhibiting the growth of M. furfur and C. albicans. Petroleum ether concentration (80 %) inhibited the growth of E. coli while C. acnes and M. furfur were inhibited at 20 % petroleum ether concentration; C. albicans was inhibited at 10 % concentration. The minimum inhibitory concentration of African walnut oil and petroleum ether extract revealed that 500 and 250 mg/mL were the least concentrations that prevented the growth of bacteria after 24 h incubation. Keyword: African walnut oil, Tetracarpidium conophorum, physical properties, chemical composition, antimicrobial activity, skin infections, agar well diffusion method, extracts, MIC